Marketing Capabilities Development in Small and Medium Enterprises: Implications for Performance - Santos-Vijande, Leticia (2012)
The purpose of the research is to analyze the organizational antecedents of marketing capabilities and their impact on business performance using a sample of small and medium enterprises (SMEs). More specifically, the research analyzes the effect of the organizations’ internal marketing (IM) practices on the employees’ implementation of a coordinated set of commercial abilities crucial to firms’ competitiveness. Results of the research indicate that IM, or the management of human resources as internal organizational clients, is a key determinant in motivating employees effectively to develop both strategic and operational marketing capabilities. Marketing capabilities exert a significant and positive effect on clients’ satisfaction and loyalty, which ultimately lead to better organizational performance in terms of sales, profit, and market share. The research also contributes to the scarce amount of empirical evidence on the positive and direct effect of IM strategies on business performance.